Campanella and the Mondo Nuovo: a Late Renaissance Geopolitics - Rojas-Olmedo, Pablo (2025)
he nucleus of Campanella’s political theory has as its center the aim of a universal or imperial government inspired by a theological necessity. The empire has as its purpose the unity of the men and women of the world under Catholicism in the plurality of territories and customs. The discovery of the New World brought him the responsibility for the salvation of the souls of its population, in addition to the possibility of thinking effective strategies for the political dominance of the American land. The hypothesis that will guide the argumentation will indicate that the interest of the Calabrian friar thought about America can be divided in two: on the one hand, an epistemological rupture that highlights a new empirical attitude (§2), and on the other hand, the need to include it under the empire government of the world (§3-4). Considering and pointing out the obvious influences of the American chronicles of the time, the works of the humanist Francisco López de Gómara and the jesuit José de Acosta.